Slovar zvonjenja in pritrkavanja - Ambrožič, Matjaž (ZRC SAZU, Založba ZRC, 2017)
Bell ringing and bell chiming are presenting a valuable part of Slovenian cultural heritage, which is reflected in an extremely rich vocabulary that is part of our everyday reality and communication. The dictionary brings about 1035 expressions from the fields of amateur and professional engagement with bell ringing and bell chiming. It unveils the bells as a versatile musical instrument of cultural, ethnomusicological, artistic and also, in the case of older bells, of historical value. In addition to the modern terms, it contains some past terms, as well as many dialectal words, including the ones from vocabulary of Slovenians living in the neighboring countries. The monolingual design of the explanatory terminological dictionary is exceeded by the addition of English equivalents and the English-Slovene dictionary. This enables that also international scholars and bell experts gets acquainted with the special features of Slovenian bell ringing and bell chiming. The dictionary is intended for professionals from different fields of science, as well as for bell ringing experts, bell chimers, as well as everyone attracted by the sounds of our soundscapes. The authors of the dictionary would like to encourage new research of this kind, and especially would like that campanology gets appropriate position in the field of profession and science in Slovenia and abroad.